2021
DOI: 10.1021/acs.jctc.1c00788
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Biomolecular Structures by the Nano-LEGO Approach: Pick the Bricks and Build Your Geometry

Abstract: The determination of accurate equilibrium molecular structures plays a fundamental role for understanding many physical–chemical properties of molecules, ranging from the precise evaluation of the electronic structure to the analysis of the role played by dynamical and environmental effects in tuning their overall behavior. For small semi-rigid systems in the gas phase, state-of-the-art quantum chemical computations rival the most sophisticated experimental (from, for example, high-resolution spectroscopy) res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
169
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 61 publications
(172 citation statements)
references
References 87 publications
3
169
0
Order By: Relevance
“…The lack of isotopic substitutions on F atoms, which prevents a reliable determination of the structural parameters involving them, can be overcome by using two strategies: the non-determinable parameters can be constrained to an accurate theoretical value or, alternatively, one can resort to the use of the predicate observations method, which uses estimates of structural parameters as additional input data [ 74 ]. In addition to being more flexible with respect to treating theoretical parameters as rigid constraints, it should lead to more precise results [ 75 , 76 ]. In the present work, this second method has been adopted with predicates for the C3−F4 and C3−F6 bond lengths and C2C3F4 and C2C3F6 angles taken from the CCSD(T)/CBS+CV gradient scheme results.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of isotopic substitutions on F atoms, which prevents a reliable determination of the structural parameters involving them, can be overcome by using two strategies: the non-determinable parameters can be constrained to an accurate theoretical value or, alternatively, one can resort to the use of the predicate observations method, which uses estimates of structural parameters as additional input data [ 74 ]. In addition to being more flexible with respect to treating theoretical parameters as rigid constraints, it should lead to more precise results [ 75 , 76 ]. In the present work, this second method has been adopted with predicates for the C3−F4 and C3−F6 bond lengths and C2C3F4 and C2C3F6 angles taken from the CCSD(T)/CBS+CV gradient scheme results.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The equilibrium geometry obtained by using the large cc-pV5Z basis set is also in agreement with the SE structure, even though larger deviations than those for composite methods can be noted. A strikingly accurate equilibrium geometry is obtained by augmenting the PW6B95 and rev-DSDPBEP86 results through the nano-LEGO approach [ 76 ]. In fact, whereas for the bare functionals, differences as large as 6–7 mÅ are obtained, as can be seen in Table S1 of the Supplementary Materials (SM) , the nano-LEGO procedure lowers the deviations to 1.2 mÅ, thus reaching the same accuracy as the CCSD(T)-based composite methods but at a far lower computational cost.…”
Section: Results and Discussionmentioning
confidence: 99%
“…It is well documented that B2 equilibrium geometries are remarkably accurate [ 32 ]; nonetheless higher level calculations performed on small model systems can provide information to correct the structures of larger molecules obtained at lower computational levels following the template molecule and/or linear regression approaches (referred to in the following as TMA and LRA, respectively) [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, methods rooted in the density functional theory (DFT) have emerged as the methods of choice for medium- to large-size molecular systems not amenable to the most accurate (but also prohibitively expensive) wave-function methods. In this connection, several studies have shown that double-hybrid functionals in conjunction with partially augmented triple-zeta basis sets are particularly reliable for geometrical structures, vibrational frequencies and several other spectroscopic properties [ 7 , 12 , 13 ]. On these grounds, we have performed a comprehensive study of several prototypical nitroxide radicals using as benchmarks either available experimental data or state-of-the-art QC results.…”
Section: Introductionmentioning
confidence: 99%
“…In this connection, the B2PLYP-D3/ maug-cc-pVTZ model (Grimme, 2006;Papajak et al, 2009) employed in our earlier studies has recently been replaced by the rev-DSD-PBEP86 functional (Santra et al, 2019) in conjunction with the jun-cc-pVTZ (Papajak et al, 2011) basis set (such a functional-basis combination is shortly denoted as rev-DSD in the following), which usually delivers improved results (with respect to the former) for transition states and non-covalent complexes without reducing the accuracy of other parameters. When more accurate geometries are sought (especially in connection with spectroscopic properties or intermolecular distances of pre-reactive complexes), more accurate quantum-chemical approaches (vide infra) or a "LEGO bricks" approach can be employed (Ceselin et al, 2021;Melli et al, 2021).…”
Section: Reaction Mechanisms: Barriers and Thermochemistrymentioning
confidence: 99%